Morfometria e crescimento alométrico de larvas de duas espécies de peixes migradores de grande porte, nativos da América do Sul - Rodrigues, Adilson (2010)
The aim was to detect morphometric differences in the stages of larval development Hemisorubim platyrhynchos and Pseudoplatystoma corruscans and allometric growth in these two fish species of ecological and economic relevance in South America Larvae were separated into six stages of development ontogenetic larval (yolk sac larval, preflexion, initial of flexion, flexion, end of flexion and post flexion). That allowed Landmarks grouping them in three series of geometric distances. Was applied to PCA for each series of distances between different stages of larval development of both species to examine the morphometric patterns (similar or not). The factorial analysis of variance (species and stage of development) was used above retained axes of PCA for interpretation of data and test the possible differences. To verify the existence of allometric pattern in species, the scores generated by the first axis of PCA was used to estimate the multivariate allometric coefficients. The series I from PCA segregated (H. platyrhynchos and P. corruscans) the species and stages (larval yolk and pre-flexion). In the series II H. platyrhynchos showed no differences between the larval stages, but for P. corruscans was marked development from the flexion stage to the late flexion allowing a separation of H. platyrhynchos. In post-flexion stage (series III) morphometric discrimination between species was not evident. In relation to the allometric growth, the increase regions-median cephalic and caudal was accentuated in the early stages of both species in question, tending to isometry as the species developed. This work was possible morphometric differentiation of species in larval stages of development, aside from a post-flexion.